PREPARATION OF PROFESSIONAL TEACHERS FOR PEDAGOGICAL ACTIVITIES - Ko'charov, Sardorbek (Физико-технологического образование, 2022)
In the e-learning environment, special attention is paid to preparing a technology teacher for professional work. The importance of using information and communication technologies is discussed.